Evaluation of the Waters MassTrak LC–MS/MS Assay for Tacrolimus and a Comparison to the Abbott Architect Immunoassay. Issue 3 (June 2016) - Saitman, Alec; Metushi, Imir G.; Mason, Donald S.; Fitzgerald, Robert L.
Abstract : Background: Tacrolimus (Prograf, Advagraf, and FK-506) is the most commonly prescribed calcineurin inhibitor after kidney and liver transplantation. The use of tacrolimus (in conjunction with other drugs) has successfully contributed to the maintenance of solid organ allografts; however, it also exhibits toxic side effects. Therapeutic drug monitoring of tacrolimus is used as an aid to achieve drug concentrations within a narrow therapeutic window. Methods: The Waters MassTrak Immunosuppressants assay (LC–MS/MS) for the quantification of tacrolimus in whole blood was evaluated for precision, linearity, lower limit of quantification, matrix effects, and accuracy. A method comparison with the Abbott Architect Tacrolimus immunoassay was also performed. Results: The mean concentration (nanograms per milliliter) and coefficient of variation for low, mid, and high patient pools were 0.6% ± 19.9%, 16.0% ± 5.4%, and 31.2% ± 5.8%, respectively. The MassTrak assay was linear from 0.5 to 30.0 ng/mL. Although the MassTrak and Architect assays correlated well (R 2 = 0.97) for patient samples, the MassTrak assay displayed an average negative bias of 18.5% versus Architect (range of 0.0%–36.7%). Analysis of a certified tacrolimus reference material in human whole blood [European Reference Materials (ERM)-DA110a, LGC Standards] on both platforms failed to completely explain the observed difference for patient samples. Conclusions: Two widely used assays for therapeutic drug monitoring of tacrolimus are not in agreement with one another. Care should be exercised when interpreting results generated on these 2 assay platforms.